MACROECONOMIC POLICY GUIDELINES IN THE EUROPEAN UNION COUNTRIES - ALEXANDRU PADUREAN; ELENA BUGA (Challenges of the Knowledge Society)
In recent years, some European Union countries have made progress in economic convergence plan, but in others some special challenges took place. Economic and financial crisis has intensified some of the problems faced by these countries, causing undesirable developments. Measures taken by Member States differ from state to state, depending on the economic reality of each.